Pharmacotherapy and antimicrobial resistance in patients hospitalized in an intensive care unit (Research, Society and Development, 2023)
The present study aims to identify the profile of antibacterial resistance in pharmacotherapy used in patients in an Intensive Care Unit (ICU) of a private hospital in Cascavel – PR. The objective is to identify the main resistant bacteria, the antibiotic therapy used and define the resistance profile of the identified microorganisms. This study is characterized as a retrospective cross-sectional observational study, based on exams carried out on patients admitted to an ICU of a private hospital in Cascavel – PR, from 2020 to 2021. The results were a higher prevalence of infection in male patient’s male (65.42%) and a higher rate of cases over 49 years of age. The biological sample used in both years analyzed was tracheal secretion with 61.82% in 2020 and 48.08% in 2021. and a total of 14 species of bacteria isolated. A prevalence of Klebsiella pneumoniae was observed with 36.64% of the total positive cultures in the period, followed by Pseudomonas aeruginosa (18.69%) and Staphylococcus aureus (11.21%). Regarding antibiotic resistance, K. pneumoniae presented an average of 62% to the drugs used in its treatment, accompanied by P. aeruginosa with an average of 57% resistance, and S. aureus presented 73.5%. The high prevalence of antibiotic resistance in the ICU of this institution suggests the need for improved surveillance and control of infections. This study offers data to improve clinical practice as well as the management of infections in the inpatient sector.